Biodisponibilidade de minerais de farinhas de carne e ossos para a Tilápia do Nilo - Moura, Lorena Batista de (2014)
Bioavailability of calcium (Ca), phosphorus (P), sodium (Na), potassium (K) and magnesium (Mg) of meat and bone meal with different levels of crude protein (CP) were evaluated. An in vivo digestibility trial was carried out with 180 juveniles of Nile tilapia (32.65 ± 4.52 g), GIFT strain, divided into conical tanks. Five meat and bones meals with 30.90, 35.26, 38.06, 41.38 and 44.36% CP were evaluated in a completely randomized design with five treatments and three replications. To determine the apparent digestibility coefficients (ADC) a reference diet based on soybean meal and poultry meal by product with approximately 3,120 kcal DE.kg-1 and 32% of CP was elaborated. The test diets were composed of 70% of reference diet and 30% of each meat and bone meal. The values of ADCs were submitted to variance analysis and in case of significance were then submitted to polynomial regression analysis (P < 0.05). Analysis of linear correlation between the chemical composition of the meals and ADC of nutrients and minerals was also performed. ADCs mean values of the minerals Ca, P, Na, K and Mg varied between -2.35 and 26.75; 3.7 and 55.31; 37.83 and 82.77; -0.72 and 23.04; 24.38 and 331.84 %, respectively. Effect of ash and CP on ADC of Ca and P, and on the ADC of dry matter (DM) were observed. Positive correlation between the CP and the ADC of all minerals analyzed was observed except for K and Mg, which showed a positive correlation with the ash content of the meals. The ADCs of Ca, P and Na, showed a negative correlation with the ash content. The ADC of DM was positively correlated only with the CP and the mineral Na. The ADC of Ca and P were negatively correlated with the levels of minerals Ca, P and Mg. The meat and bone meals with 46.37 % CP showed higher ADC of nutrients and minerals. The meat and bones evaluated can be used as a source of minerals for Nile tilapia.